Comparison of six-week flywheel and traditional resistance training on deceleration and dynamic balance in elite badminton players - Yuan, S.; Lu, Z.; Tan, S.; Zhang, Z.; Jing, S.; Liu, H.; Zhou, Z.; Bao, Z. (Frontiers in Physiology, 2025)
Introduction: The aim of this study was to compare the effects of flywheel resistance training (FRT) and traditional resistance training (TRT) on deceleration and dynamic balance performance in elite badminton players.